Oncoplastic Approaches to Breast Conservation - Dennis R. Holmes; Wesley Schooler; Robina Smith (International Journal of Breast Cancer)
When a woman is diagnosed with breast cancer many aspects of her physical, emotional, and sexual wholeness are threatened. The quickly expanding field of oncoplastic breast surgery aims to enhance the physician commitment to restore the patient's image and self-assurance. By combining a multidisciplinary approach to diagnosis and treatment with oncoplastic surgery, successful results in the eyes of the patient and physician are significantly more likely to occur. As a way to aid oncoplastic teams in determining which approach is most suitable for their patient's tumor size, tumor location, body habitus, and desired cosmetic outcome we present a review of several oncoplastic surgical approaches. For resections located anywhere in the breast, the radial ellipse segmentectomy incision and circumareolar approach for segmental resection are discussed. For resections in the upper or central breast, crescent mastopexy, the batwing incision, the hemibatwing incision, donut mastopexy, B-flap resection, and the central quadrantectomy are reviewed. For lesions of the lower breast, the triangle incision, inframammary incision, and reduction mastopexy are discussed. Surgeons who are interested in adding oncoplastic breast conserving therapies to their skill sets are encouraged to implement these surgical techniques where applicable and to seek out breast fellowships or enhanced training when appropriate.